Deliberating on Environmental Education and its Practices During the COVID-19 Pandemic - Sharma, Yukti (SCHOOL SCIENCE, 2021)
The article deliberates on the epistemological debate that exists in the field of environmental education in the context of the present pandemic situation. Humans have always considered themselves to be the most evolved species so far so that the relationship they shared with their environment was also being defined by them as a phenomenon that existed because humans existed. Although, the contrary view existed but the anthropocentric worldview dominated even after being challenged by the other worldviews. The advent of the pandemic situation affected the human life more than any other life on earth. Moreover, the basic needs required for human survival during the pandemic conflicted with the practices that have been prescribed through the anthropocentric view in environmental education. This raises crucial questions on the worldview that had been predominating the field. Hence, the article revisits and deliberates on the existing perspectives of environmental education and its practices taking the context of COVID-19. pandemic. The two major positions/worldviews underlying the core of environmental education — anthropocentric and the eco-centric have been discussed taking relevant cases and arguments. The article corroborates the need for operationalising the eco-centric view in environmental education.